The Peningkatan Efisiensi Energi Listrik Melalui Pengelolaan AC dan Lampu Berbasis Counter - Dimas Rahmat Prasetya; Abdul Multi (Institut Sains dan Teknologi Nasional, 2025)
Global warming caused by greenhouse gas emissions has become a critical issue that needs urgent attention. One of the major contributing factors is electricity consumption in office buildings, particularly from air conditioning (AC) systems and lighting. Therefore, energy efficiency in office buildings must be optimized to reduce environmental impact while minimizing operational costs. This study applies a technical approach to optimizing AC and lighting systems at the headquarters of a mining company. The implemented measures include managing electrical systems based on actual energy needs, utilizing energy-efficient devices, and designing systems that reduce electrical loads. Collaboration with ISTN students further enriches the solutions through the application of relevant knowledge. The study results show that energy optimization achieved a savings of 1,397.94 kWh per month, reducing electricity consumption by up to 62.9% and lowering the company's operational costs by Rp 2,374,892.80 per month. These efficiency measures support corporate sustainability goals by improving budget efficiency. Keywords: Global warming, energy efficiency, electrical systems, AC and lighting, sustainability